EDEM-based study on the adjustable feeding parameters of square bale maize straw bale-breaking device - Tiejun Wang; Tinghe Zhang; Shuai Yu; Hongguang Cui; Ruili Wang (PLoS ONE, 2025)
One of the primary challenges faced by small rubbing filament machines is the significant variability in material sizes, particularly in the feeding direction. This variability complicates the processing of locally baled straw with a single device. To address this issue, an adjustable feeding and bale-breaking device was developed and tested to enhance the filamentous performance of baled straw. The machine integrates a series of bale-breaking knives along with a pair of feeding and bale-breaking rollers. This paper presents an overview of the machine’s structure and operating principles, alongside an analysis of the forces acting on the straw within the device, which informed the design of key components and devices. A discrete element simulation model suitable for square baled-straw has been established, providing a research foundation for the subsequent optimization of device design parameters. Effects of motor bale-breaking roller rotating speed (x1), bale-breaking roller height (x2) and bale-breaking knife quantity (x3) on the productivity of bonding bond destruction rate (Y1) and the particle average speed (Y2) were explored. Three-dimensional quadratic regression orthogonal rotation central combination experiment method combined with response surface method was used to conduct experiments and explore the interaction effects of influence factors on indicators. A regression model of influence factors and evaluation indicators was established through the analysis of variance. The significant factors affecting Y1 were ordered of x1, x2, x3, and the significant factors affecting Y2 were ordered of x2, x3, x1. In the interaction of factors, x1x2 and x2x3 had an extremely significant impact, and x1x3 had a significant impact on Y1; x1x2, x1x3 and x2x3 had a significant impact on Y2. The optimal structure and working parameters combination were determined to be 1448 rpm for x1, 268 mm for x2, and 14 pieces for x3. Verification experiments demonstrated that the actual values were 96.95% for the straw rubbing rate and 235.13 kg/(kW·h) for the per unit power productivity. The operation of the adjustable feeding and bale-breaking device developed in this study proved effective in enhancing productivity and breaking performance during the feeding of baled straw. It successfully met the design requirements for the grain size necessary for the comprehensive utilization of straw. Overall, this research establishes a foundational basis for the further development of a small, multipurpose straw rubbing filament machine.